Specific polarizability of sand–clay mixtures with varying ethanol concentration. Issue 6 (1st October 2017) - Sharma, Sundeep; Slater, Lee; Ntarlagiannis, Dimitrios; Werkema, Dale; Szabo, Zoltan
ABSTRACT: We utilise a concept of specific polarizability ( c s ), represented as the ratio of mineral‐fluid interface polarization per pore‐normalised surface area S p, to demonstrate the influence of clay‐organic interaction on complex conductivity measurements. Complex conductivity measurements were performed on kaolinite‐ and illite‐sand mixtures as a function of varying ethanol (EtOH) concentration (10% and 20% v/v). The specific surface area of each clay type and Ottawa sand was determined by nitrogen‐gas‐adsorption Brunauer‐Emmett‐Teller method. We also calculated the porosity and saturation of each mixture based on weight loss of dried samples. Debye decomposition, a phenom‐enological model, was applied to the complex conductivity data to determine normalised chargea‐bility ( m n ) . Specific polarizability estimates from previous complex conductivity measurements for bentonite‐sand mixtures were compared with our dataset. The c s for all sand–clay mixtures decreased as the EtOH concentration increased from 0% to 10% to 20% v/v. We observe similar c s responses to EtOH concentration for all sand–clay mixtures. Analysis of variance with a level of significance a = 0.05 suggests that the suppression in c s responses with increasing EtOH concentration was statistically significant for all sand–clay mixtures. On the other hand, real conductivity showed only 10% to 20% v/v changes with increasing EtOH concentration. The c s estimates reflect the sensitivity of complex conductivity measurements to alteration in surface chemistry at available surface adsorption sites for different clay types, likely resulting from ion exchange at the clay surface and associated with kinetic reactions in the electrical double layer of the clay‐water‐EtOH media. Our results indicate a much larger influence of specific surface area and ethanol concentration on clay‐driven polarization relative to changes in clay mineralogy.